Perancangan Relayout Tata Letak Fasilitas Guna Mengurangi Biaya Material Handling pada UKM Tahu “SRT” Kediri - Astria Hindratmo; Chendrasari Wahyu Oktavia (Journal of Research and Technology, 2022)
"SRT" is the name of an SME that produces typical Kediri tofu which is located in Klepek Village, Kediri Regency. The “SRT” tofu production process goes through several stages with the help of tofu production equipment and facilities. The condition of UKM Tofu has a land area of ​​about 130 m2, but the layout of the production facilities is less effective. It was caused by several production facilities that were quite far apart and several facilities’ layout were not sequential which resulted too much material handling on production process carried out by employees and quite large material handling costs. The purpose of this research was to make a redesign of the facility layout in order to reduce material handling costs. The methods used in this study were Systematic Layout Planning (SLP) and the Kaizen 5S method (Seiri, Seiton, Seiso, Seiketsu, and Shitsuke). The data used in this research was gathered through interviews and questionnaires. This study resulted a layout design proposal, the total distance of material handling per day was shortened by about 68.5 meters, and the cost of material handling (OMH) per day was more efficient, it was about 52.5%.